2001
DOI: 10.3141/1761-01
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Precast Concrete Panels to Expedite Construction of Portland Cement Concrete Pavements

Abstract: As the number of vehicles on America’s roadways continues to grow at an unprecedented rate, pavements continue to deteriorate faster and require replacement. In urban and densely populated areas, however, pavement construction can cause traffic delays, thereby increasing user costs. A method for expediting pavement construction to reduce traffic delays and user costs is therefore needed. A feasible method for expediting construction of portland cement concrete pavements through the use of precast concrete pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Increased traffic volumes on roads and highways create even greater traffic congestion during such projects. The significant increase in congestion, traffic delays and user costs as a result of construction delays are well documented (27,28). This situation is more intensified in urban and densely populated areas.…”
Section: Problem Statementmentioning
confidence: 97%
“…Increased traffic volumes on roads and highways create even greater traffic congestion during such projects. The significant increase in congestion, traffic delays and user costs as a result of construction delays are well documented (27,28). This situation is more intensified in urban and densely populated areas.…”
Section: Problem Statementmentioning
confidence: 97%
“…In the United States conducted feasibility study have shown that daily user delay costs exceed 300 000 Eur per day for 24-hour lane closure (Merritt, Mccullough, Burns, & Schindler, 2000). It results in more than 2 millions Eur per week and 0.1 billion per year.…”
Section: Introductionmentioning
confidence: 99%
“…The quality and good performance of precast concrete (PC) slabs and decks can be guaranteed because they are factory products manufactured using a steam curing method to enhance efficiency and improve productivity. Moreover, PC slab concrete pavements have been widely used for roads because of the benefits of shorter construction times and quick repairs . However, steam‐cured concrete products are reported to have been more liable to damage due to scaling than is the case with normally cured concrete products .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PC slab concrete pavements have been widely used for roads because of the benefits of shorter construction times and quick repairs. [1][2][3] However, steam-cured concrete products are reported to have been more liable to damage due to scaling than is the case with normally cured concrete products. [4][5][6] Thus, studies of the durability of steam-cured concrete products with fly ash replacement exposed to the combined deterioration of freeze-thaw cycles and de-icing chemicals have been conducted to solve such problems.…”
Section: Introductionmentioning
confidence: 99%